Pd-catalyzed chemo- and regioselective cross-coupling of two enamides. Issue 37 (14th September 2016) - Liu, Hong-Mei; Lu, Wen; Luo, Cui-Ping; Yang, Luo
Graphical abstract: Highlights: Palladium-catalyzed head-to-tail cross-coupling of enamides. Excellent chemo-/regioselective are realized. Up to 20 examples and 93% yield. Abstract: A convenient Pd-catalyzed cross-coupling of two different enamides is developed to afford the head-to-tail heterodimerization products predominately in ( Z )-configuration and up to 93% yield, with good chemo- and regioselectivity.